CARDIOPROTECTIVE EFFECT OF THE RED PALM OIL SUPPLEMENTATION ON THE CARDIAC OXIDATIVE STRESS, NITRIC OXIDE SYNTHASE AND HEART FUNCTION IN THE RATS SUFFERING FROM HYPERTENSION. (June 2018) - Bacova, B. Szeiffova; Sykora, M.; Bernatova, I.; Knezl, V.; Tribulova, N.
Abstract : Objective: We know from our previous study that myocardial protein connexin 43 (Cx43), responsible for intercellular communication, and protein kinase C epsilon which directly phosphorylates Cx43 on the serine 368, were significantly decreased in spontaneously hypertensive rats (SHR) what was also associated with increased incidence to malignant arrhythmias. Antioxidant rich red palm oil (RPO) significantly normalized all of these parameters. Therefore, we further aimed to investigate whether intake of RPO may affect endothelial dysfunction, antioxidant enzymes and heart function in SHR. Design and method: In accordance with the rules issued by the State Veterinary Administration of the Slovak Republic and European Union Council Directive 86/609/EEC we used in our experiment 3-months-old, male SHR and normotensive Wistar-Kyoto control rats fed standard rat chow without or with RPO (0.2 ml/day/5 weeks). Left ventricular tissue was used to examine expression of antioxidant enzymes such as superoxide dismutases (SOD1, SOD2) and glutathione peroxidases (GPx) as well as activity of nitric oxide synthase (NOS). Functional parameters of the heart were measured during basal conditions and at the early-phase of post-ischemic reperfusion by Langendorff-perfused system. Results: RPO supplementation significantly normalized higher blood pressure and total NOS activity as well as increased lowered expression of mitochondrial SOD2 in SHR hearts during basal condition. RPO intake resulted in the suppression of elevated heart rate, increase of reduced coronary flow and enhancement of systolic and diastolic heart function at the early-phase of post-ischemic reperfusion. Conclusions: We can conclude that SHR benefit from RPO intake due to its apparent anti-arrhythmic effects by Cx43 modulation, reduction of blood pressure, enhancement of oxidative stress and protection of heart function that was deteriorated by post-ischemic reperfusion.